Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/1754-9485.13441
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evidence for synergy between immunotherapy and radiotherapy (SITAR)

Abstract: Previous preclinical and clinical trials have shown promising antitumour activity and toxicity profile when employing the 'Synergy between Immunotherapy and Radiotherapy' (SITAR) strategy. Approximately, one in seven radiation therapy studies currently recruiting is investigating SITAR. This article reviews the range of cancers known to respond to immunotherapy and publications analysing SITAR. It sets the background for work that needs to be done in future clinical trials. It also reviews the potential toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…Toxicity remains a critical issue in combination therapies. Given the long half-lives of ICIs, RT conducted after the last dose of ICIs is still considered as combination therapy [ 137 ]. For example, it would require 3 months for durvalumab to be cleared from the system.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity remains a critical issue in combination therapies. Given the long half-lives of ICIs, RT conducted after the last dose of ICIs is still considered as combination therapy [ 137 ]. For example, it would require 3 months for durvalumab to be cleared from the system.…”
Section: Discussionmentioning
confidence: 99%
“…RT is known to synergize with the antitumor effects of PD1/PD-L1 axis blockade [ 43 , 44 ]. This probably underlies some tumor responses that extend beyond the radiation field, as in the case series by Xu et al These authors reported the impressive outcomes of two patients with mMCC progressing on PD-1 inhibitor therapy and then treated with 8 Gy-single-fraction palliative radiotherapy to some portion of the tumor masses: surprisingly, both patients rapidly experienced a marked reduction until disappearance not only of the irradiated tumor portion, but also of the distant out-of-field tumor sites [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“… 17 18 Although radiotherapy can enhance antitumour effects, its potential immunosuppressive effects can also restrain antitumour efficacy, including the upregulation of coinhibitory ligands such as PD-L1. 19 20 Combining radiotherapy with immune checkpoint blockade can overcome these immunosuppressive mechanisms and augment antitumour immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumour effect of radiation can be attributed to the induction of tumour cell death through DNA damage, but radiotherapy also has immunomodulatory effects and can stimulate the immune response through various mechanisms 17 18. Although radiotherapy can enhance antitumour effects, its potential immunosuppressive effects can also restrain antitumour efficacy, including the upregulation of coinhibitory ligands such as PD-L1 19 20. Combining radiotherapy with immune checkpoint blockade can overcome these immunosuppressive mechanisms and augment antitumour immunity.…”
Section: Discussionmentioning
confidence: 99%